2016
DOI: 10.1371/journal.pone.0154843
|View full text |Cite
|
Sign up to set email alerts
|

Abandonment of Treatment for Latent Tuberculosis Infection and Socioeconomic Factors in Children and Adolescents: Rio De Janeiro, Brazil

Abstract: BackgroundRoutine data on the use of isoniazid preventive therapy (IPT) in children and adolescents are scarce in high tuberculosis (TB) burden countries.ObjectiveTo describe the factors related to abandonment of IPT in children and adolescents with latent tuberculosis infection (LTBI) receiving routine care.MethodsRetrospective (2005–2009) descriptive study of 286 LTBI cases with indication of IPT and serviced at a pediatric hospital in the State of Rio de Janeiro, Brazil. Survival analysis of the risk of aba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 22 publications
1
21
0
9
Order By: Relevance
“…In Rio de Janeiro, in a study conducted between 2005 and 2009, missing treatment rates of children undergoing treatment for a latent infection were 25.3%. 11 In this study, it was not possible to relate absenteeism and/or stopping treatment to the use of medication or to the length of the follow-up period. Absenteeism may delay a diagnosis and, consequently, the start of treatment, which may interfere with the child's health.…”
Section: Discussionmentioning
confidence: 93%
“…In Rio de Janeiro, in a study conducted between 2005 and 2009, missing treatment rates of children undergoing treatment for a latent infection were 25.3%. 11 In this study, it was not possible to relate absenteeism and/or stopping treatment to the use of medication or to the length of the follow-up period. Absenteeism may delay a diagnosis and, consequently, the start of treatment, which may interfere with the child's health.…”
Section: Discussionmentioning
confidence: 93%
“…A recurring theme throughout the different studies was the burden of travel for caregivers of children that had been advised to complete IPT. While financial cost was an issue for some, the duration of travel from people's homes to the nearest clinic appeared to be the principal issue for many . Seasonal farming demands and other family priorities, particularly for mothers, were often recognised as more important than taking children to the clinic .…”
Section: Discussionmentioning
confidence: 99%
“…The cost of treatment itself did not appear to present as significant an issue as travel overall; however, this was also mentioned as an obstacle in some areas . Many study participants and authors indicated that enhanced access to IPT through provision at peripheral health sites in rural areas could greatly contribute to improved uptake for children in these regions who may otherwise miss out on treatment . Strategies designed to minimise cost and maximise flexibility would give families the best chance of adhering to IPT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations